Rising Cases of Hb H Disease in Iraq Highlight the Urgent Need for Pre-Pregnancy Screening: Meningkatnya Kasus Penyakit Hb H di Irak Menyoroti Kebutuhan Mendesak untuk Skrining Pra-Kehamilan - Afak Rasheed Salman Zaidi (Universitas Muhammadiyah Sidoarjo, 2024)
General background: Hemoglobin H (Hb H) disease results from mutations in three of the four α-globin genes, leading to α-thalassemia. Specific background: In Iraq, this condition is rare among alpha-thalassemia cases. The disease presents significant hematological abnormalities, impacting quality of life. Knowledge gap: Despite its rarity, few studies have characterized the hematopathological features and prevalence of Hb H disease in specific Iraqi regions. Aims: This study aimed to assess the hematological parameters and prevalence of Hb H disease among patients in Diyala province, Iraq. Results: A total of 81 patients with Hb H disease (53.18% male, 46.91% female) were registered at the Baqubah Teaching Hospital in 2023. Median patient age was 21.8 years (range 4-48). Hematological analysis revealed consistently low levels of hemoglobin (Hb) and hematocrit (HCT) compared to standard values. Mean corpuscular volume (MCV) was also significantly reduced, with 58.02% of patients presenting Hb levels below 10 g/dL. The 21-40 age group had the highest incidence (46.91%). Novelty: This study is among the few to investigate Hb H disease prevalence and hematopathological characteristics in Diyala province, revealing an unexpectedly high incidence in the 21-40 age group. Implications: These findings suggest that hematological parameters, including MCV and Hb levels, should be considered in thalassemia screening programs, particularly in pre-pregnancy assessments, to prevent the birth of children with severe forms of alpha-thalassemia and reduce Hb H disease prevalence. Highlights: Hb H disease shows low hemoglobin and MCV abnormalities. Highest incidence occurs in patients aged 21-40 years. Pre-pregnancy screening reduces severe alpha-thalassemia risk. Keywords: Hb H disease, alpha-thalassemia, hematological parameters, Diyala province, prevalence